The dynamic relationships of credit risk, profitability, and capital: Evidence from Indonesia - Sutanto, Hendra; Meiryani; Ariefianto, Moch Doddy (Asian Economic and Financial Review, 2024)
The study examines the dynamic relationships between credit risk, profitability, and capital. Credit risk is a crucial metric for bank health, affecting micro- and macro-financial stability. It is impossible to overstate the importance of effective risk management procedures for maintaining the health and stability of banks and reducing the potential threat that non-performing loans may pose. Profitability and capital, being of paramount importance in the realm of credit risk, represent intricately linked factors. While existing studies address the static linkages between credit risk, profitability, and capital in depth, there is a significant gap in our knowledge of their dynamic interactions. There exists a conspicuous void in our understanding of their dynamic interactions. To bridge this knowledge gap, our study employs a novel technique. We employ a Dynamic Common Correlated Effects (DCCE) model, leveraging a panel dataset encompassing 85 Indonesian banks, encompassing data spanning from January 2012 to September 2021. The study found that non-performing loans (NPLs) have a negative dynamic (and significant) relationship with profitability in the long run and short run, whereas capital is statistically unimportant. The equilibrating process of this dynamic relationship takes between 2.11 and 3.73 months. Our result is robust when examined across bank types but slightly different between before and during the COVID-19 era. The study contributes to understanding the relationships among credit risk, profitability, and the capital equilibrating process, and it has important implications for business practices and regulations, particularly in terms of financial stability.